Distribution of asperuloside, scandosidmethylester in plant organs of Hedyotis corymbosa (L.) Lamk (Oldenlandia corymbosa Linn) of rubiaceae family - ., Sudarsono (Indonesian Journal of Pharmacy, 2004)
Iridoid substances can be used as characteristic substances in Rubiaceae. Asperuloside and scandosidmethylesther, iridoid substances were found in Hedyotis corymbosa (L.) Lamk. (Oldenlandia corymbosa Linn). The people used several Rubiaceae plants for curing cough, rheumatic, cancer, fieber. Distribution of asperuloside and scandosidmethylesther inleaf, stem, fruit and root of Hedyotis corymbosa (L.) Lamk. has a possibility as a characteristic pattern. The aim of this research is to know the distribution profile of asperuloside, scandosidmethylesther, at the leaf, stem, fruit, and root of Hedyotis corymbosa L. (Lamk.). Trim Hill reagent was used for the qualitatve analyse of asperuloside and scandosidmethylesther and gradient system elution by high pressure chromatography was used for separation and quantitative analyses.Asperuloside content were in stem (0,146 ± 0,004 %); leaf(0,470 ± 0,020%); fruit (0,142 ± 0,005%); root(0,560 ±0,013%) and scandosidmethylester content were in stem (0,618 ± 0,22); leaf (0,156 ± 0,007); fruit(0,037 ± 0,002); root (0,136 ± 0,006).Key words: Asperuloside, scandosidmethylesther, distribution Hedyotis corymbosa (L.)Lamk.(Oldenlandia corymbosa Linn)